The Florida Fertilizer Label - Jerry B. Sartain (EDIS, 2009)
Revised! SL-3, a 5-page fact sheet by J.B. Sartain, is included in the Florida Lawn Handbook and the Florida Master Gardener Handbook. It describes the information required by law to be shown on the fertilizer label in Florida. Published by the UF Department of Soil and Water Science, October 2008.